Measurements of Salivary Alpha Amylase and Salivary Cortisol in Hominoid Primates Reveal Within-Species Consistency and Between-Species Differences - Behringer, Verena (Public Library of Science, 2013)
Salivary alpha amylase (sAA) is the most abundant enzyme in saliva. Studies in humans found variation in enzymatic activity of sAA across populations that could be linked to the copy number of loci for salivary amylase (AMY1), which was seen as an adaptive response to the intake of dietary starch. In addition to diet dependent variation, differences in sAA activity have been related to social stress. In a previous study, we found evidence for stress-induced variation in sAA activity in the bonobos, a hominoid primate that is closely related to humans. In this study, we explored patterns of variation in sAA activity in bonobos and three other hominoid primates, chimpanzee, gorilla, and orangutan to (a) examine if within-species differences in sAA activity found in bonobos are characteristic for hominoids and (b) assess the extent of variation in sAA activity between different species. The results revealed species-differences in sAA activity with gorillas and orangutans having higher basal sAA activity when compared to Pan. To assess the impact of stress, sAA values were related to cortisol levels measured in the same saliva samples. Gorillas and orangutans had low salivary cortisol concentrations and the highest cortisol concentration was found in samples from male bonobos, the group that also showed the highest sAA activity. Considering published information, the differences in sAA activity correspond with differences in AMY1 copy numbers and match with general features of natural diet. Studies on sAA activity have the potential to complement molecular studies and may contribute to research on feeding ecology and nutrition.